2012
DOI: 10.1016/j.ejvs.2012.05.016
|View full text |Cite
|
Sign up to set email alerts
|

An Association between Chronic Obstructive Pulmonary Disease and Abdominal Aortic Aneurysm beyond Smoking

Abstract: This study confirms an association between AAA and COPD and shows that this association is independent from smoking. Findings also demonstrate that COPD is under-diagnosed in AAA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
(21 reference statements)
3
32
1
Order By: Relevance
“…In PAD patients, a relatively severe progression of atherosclerotic disease is therefore likely to be responsible for the similar survival compared to the much older AAA patients, and the poor prognosis compared to the matched general population. Of note, COPD-related death was more frequent among AAA patients, which may be due to a common -genetically determined-defect in the extracellular matrix [28,29]. This further supports the divergence in pathophysiology between aneurysmal and occlusive vascular disease.…”
Section: Discussionsupporting
confidence: 58%
“…In PAD patients, a relatively severe progression of atherosclerotic disease is therefore likely to be responsible for the similar survival compared to the much older AAA patients, and the poor prognosis compared to the matched general population. Of note, COPD-related death was more frequent among AAA patients, which may be due to a common -genetically determined-defect in the extracellular matrix [28,29]. This further supports the divergence in pathophysiology between aneurysmal and occlusive vascular disease.…”
Section: Discussionsupporting
confidence: 58%
“…Moreover, patients with AAA had a more cumulative smoking duration than those without AAA. Meijer et al [8] suggested that there was an association between COPD and AAA that was independent of the smoking status and that COPD was more Using the national data, our preliminary study aimed to detect a possible association between COPD and AAA as there is no such published report in our country. Our results are consistent with those reported in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…Major risk factors for the AAA development include an age of >65 years, smoking, HT, and a presence of a vascular disease [1][2][3]. In recent years, COPD has been accepted to be a predisposing factor for AAA development [4,[6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies [20][21][22][23][24][25][26][27] have suggested that chronic obstructive pulmonary disease (COPD) is independently and positively associated with AAA presence. For instance, the multivariate logistic regression analysis in a recent case-control (271 and 1,387 patients with and without AAA, respectively) study by Song and Park [25] identifi ed COPD as an independent predictor for the risk of AAA (adjusted OR, 1.35; 95% CI, 1.07 to 1.72; P = 0.013).…”
Section: Discussionmentioning
confidence: 99%